Semen Parameters and Hormaone Profile of Men Investigated for Infertility at Midland Fertility Centre, Ilorin, Nigeria - Jimoh, A.A.G.; Olawuyi, T.S.; Omotoso, G.O.; Oyewopo, A.O.; Dare, J.K. (Journal of Basic & Applied Sciences, 2012)
This study aimed at comparing the semen parameters and pattern of endocrine abnormalities in patients investigated for male infertility in our fertility centre. Hormonal assays and semen analysis were carried out, from February 2008 to April 2010. Three hundred and sixteen (316) men were evaluated out of which forty-five (45) underwent hormonal assessment, because of the abnormalities in their sperm count. Sixteen (35.6%; 16 out of 45) of the subjects were azoospermic; twenty-three (23 out of 45; 51.1%) were oligospermic with sperm count less than 20 million sperm cell/ ml; and six (n=6; 13.3%) of the subjects were normospermic, with sperm count greater than 20 million sperm cell/ ml. The mean values of the hormonal assays for azoospermia were: 21.84±1.94 (luteinizing hormone), 14.14±4.4 (follicle-stimulating hormone), 23.95±17.43 (testosterone), and 15.03±2.91 for prolactin. Hormonal assays for patients having oligospermia were as follow: luteinizing hormone (LH) 12.56±3.90, follicle-stimulating hormone (FSH) 5.96±1.17, testosterone 10.13±2.40 and prolactin 13.42±2.43, while normospermic patients had the following hormone levels: LH: 7.72±3.90, FSH: 2.93±.74, testosterone: 17.00±3.36 and, prolactin: 12.45±2.16. We conclude that infertile men with low sperm count may not always present with abnormal hormone profiles; and, male factor, in this environment, contributes a high percentage to infertility.